Aplikasi Pengenalan Objek Wisata Rupang Satya Kalama Maha Vihara Duta Maitreya Batam Berbasis Augmented Reality Studi - Herdaya, Ajita Prajna (Fakultas Komputer - Universitas Universal, 2024)
The purpose of this research is to enhance tourist attraction through the implementation of Augmented Reality (AR) technology at specific tourist destinations, focusing on the case study of the Graha Satya Kalama Maha Vihara Duta Maitreya statue. The research method involves analyzing the potential tourist appeal and implementing AR to enhance the visitor experience. By developing a dedicated AR application, visitors can access interactive information and additional visual elements while around the statue. The results of this study are expected to demonstrate that AR implementation can enhance tourist attraction by providing a more engaging and informative experience. This research contributes to innovative development in the tourism sector, particularly in leveraging AR technology to enrich the visitor experience at cultural and religious destinations like Maha Vihara Duta Maitreya